2020
DOI: 10.1080/09638288.2020.1717650
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and short-term effects of Activity Coach+: a physical activity intervention in hard-to-reach people with a physical disability

Abstract: Purpose: Existing physical activity interventions do not reach a considerable proportion of physically disabled people. This study assessed feasibility and short-term effects of Activity Coachþ, a communitybased intervention especially targeting this hard-to-reach population. Methods: Feasibility was determined by reach, dropouts, and compliance with the protocol. Physical activity was measured with the Activ8 accelerometer and the adapted SQUASH questionnaire. Health outcomes were assessed by body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
1
1
Order By: Relevance
“…To the best of our knowledge, this is the first prospective cohort study that considers all dose characteristics (duration, setting, intensity, mode and frequency) of PA in a large heterogeneous population of adults with physical disabilities/chronic diseases. Compared with previous studies (self-reported PA in specific disability groups and in heterogeneous disability groups), our participants were more active in total PA, MVPA and leisure time PA 8 20 22 40–45. Furthermore, the proportion of participants adhering to the aerobic component of the WHO PA guideline (>150 min of moderate PA, >75 min of vigorous PA or combination of both) is higher in our population compared with previous research (68%–74% vs 35%–60%) 8 46–48.…”
Section: Discussioncontrasting
confidence: 81%
“…To the best of our knowledge, this is the first prospective cohort study that considers all dose characteristics (duration, setting, intensity, mode and frequency) of PA in a large heterogeneous population of adults with physical disabilities/chronic diseases. Compared with previous studies (self-reported PA in specific disability groups and in heterogeneous disability groups), our participants were more active in total PA, MVPA and leisure time PA 8 20 22 40–45. Furthermore, the proportion of participants adhering to the aerobic component of the WHO PA guideline (>150 min of moderate PA, >75 min of vigorous PA or combination of both) is higher in our population compared with previous research (68%–74% vs 35%–60%) 8 46–48.…”
Section: Discussioncontrasting
confidence: 81%
“…PA levels of the Canadian participants were generally low, but comparable to findings from other studies on measured self-reported PA among people with physical disabilities [9,10,13,45]. In contrast, PA levels of Dutch participants were high compared to other Dutch studies on self-reported PA among people with physical disabilities and/or chronic diseases [46][47][48]. The Dutch Adapted-SQUASH may overestimate participants' PA levels more than the IPAQ-SF because the Adapted-SQUASH includes items on various PA settings.…”
Section: Physical Activitysupporting
confidence: 76%
“…Therefore, the management of the instructor who guides the disabled or the evaluation of the instructor's ability should be prioritized ( 44 ). In particular, the ability of the instructor is more important for exercise ( 45 ). In elite games, the ability of the instructor determines whether the team will win or lose.…”
Section: Discussionmentioning
confidence: 99%